The usefulness of patient-specific 3D nasal silicone implant using 3D design and order form - Lee I; Ohba N; Lee H; Lee KS; Lee M (Dove Medical Press, 2022)
Inhee Lee,1 Norihiro Ohba,2 Hyejeong Lee,3 Kyu-Sung Lee,1,* Munjae Lee4,* 1Department of Medical Device Management and Research, SAIHST, Sungkyunkwan University, Seoul, 06355, Republic of Korea; 2Primo Azabu-juban Clinic, Minato Ku, Tokyo, Japan; 3The hills Aesthetic Surgical Clinic, Seoul, Republic of Korea; 4Department of Medical Humanities and Social Medicine, Ajou University School of Medicine, Suwon, Gyeonggi-do, Republic of Korea*These authors contributed equally to this workCorrespondence: Munjae LeeDepartment of Medical Humanities and Social Medicine, Ajou University School of Medicine, Suwon, Gyeonggi-do, Republic of Korea, Email emunjae@ajou.ac.krPurpose: The need for customized implants has continuously increased, but patient-specific silicone implants are not yet commonly used in the plastic surgery market. We sought to validate the effectiveness of a 3D customized nasal implant design in terms of design and lead time compared with a manually customized implant by a surgeon.Materials and Methods: Based on the computed tomography (CT) findings of 15 patients who planned rhinoplasty, a surgeon wrote order forms reflecting the surgical plan and subsequently designed implants manually using epoxy on a 3D printed skull. Separately, engineers analyzed the CT findings and designed 3D implants based on the order forms.Results: Epoxy designs were 3D-scanned, converted into a stereolithography format and compared with 3D implant designs to assess which method had a smaller margin of error as per the preoperative order form. Moreover, the lead time in all steps are compared. Nasion thickness, tip thickness, glabella starting point, glabella width, radix width, and total volume were comparatively analyzed. In all parameters, the error rate of the 3D design is relatively lower than that of the epoxy design. The former also had a lower total volume and a faster manufacturing time.Conclusion: With novel 3D customized nasal implants, the limitations of ready-made silicone implants are addressed, and it is now possible to preoperatively design implants more accurately, quickly, and conveniently.Keywords: 3D customized silicone implant, rhinoplasty, silicone, prosthesis and implants, patient-specific implant